URGENSI MENINGKATKAN SENSITIVITAS BUDAYA DALAM LAYANAN KONSELING PADA KONSELOR PEMULA - Fanny Rizkia Farandini; Muwakhidah Muwakhidah; Azra Fidela Adristi; Cristin Sagita Damayanti; Mahendra Adi Saputra; Fanny Rizkia Farandini; Muwakhidah Muwakhidah; Azra Fidela Adristi; Cristin Sagita Damayanti (Universitas Negeri Malang, 2024)
Abstract: Counseling is a process of interaction between a counselor and a client that aims to help the client achieve better self-understanding, solve problems, and make informed decisions. In counseling practice, it is important for counselors to have cultural sensitivity in order to understand and appreciate clients' cultural diversity. This is especially important for novice counselors who are just starting their counseling practice. This study aims to increase the understanding for novice counselors of the importance of cultural sensitivity of counselees with diverse cultural backgrounds of counselees. This research used a descriptive qualitative approach through a literature study, reviewing 20 articles published within the last 5 to 10 years. It resulted in 5 key articles that affirmed the importance of cultural awareness and counselor competency development in cross-cultural counseling. The results showed several important points related to the urgency of increasing cultural sensitivity for novice counselors 1) Counselor Cultural Awareness 2) Cultural Knowledge and Skills 3) Multicultural Counseling Knowledge 4) Multicultural Counseling Competence (MCC)